2019
DOI: 10.1021/acsphotonics.8b01355
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Topology of Photonic Systems with Transparent Conducting Oxides

Abstract: Precise control over photonic states can be achieved in pre-engineered materials, like photonic crystals and meta-structures. However, high fabrication precisions are required due to the sensitivity of such states to different perturbation channels. Hence photonic states that immune to disorder in the system is in high demand. In this work, we propose a hybrid platform that integrates tunable transparent conducting oxides (TCOs) and a standard silicon-on-insulator waveguide technology, to achieve ultrafast all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Therefore, reconfigurable topological systems that support topological phase transitions that can be manipulated are essential. Dynamic control of topological phase transitions has been achieved using liquid crystals 228 , a phase-change material under temperature variation 229,230 and transparent conducting oxides under optical pumping 231 . A reconfigurable photonic topological system that supports selective propagation of topological edge modes under mechanical modulation was demonstrated using a bianisotropic photonic crystal 150 .…”
Section: Topological Photonics Towards Applicationsmentioning
confidence: 99%
“…Therefore, reconfigurable topological systems that support topological phase transitions that can be manipulated are essential. Dynamic control of topological phase transitions has been achieved using liquid crystals 228 , a phase-change material under temperature variation 229,230 and transparent conducting oxides under optical pumping 231 . A reconfigurable photonic topological system that supports selective propagation of topological edge modes under mechanical modulation was demonstrated using a bianisotropic photonic crystal 150 .…”
Section: Topological Photonics Towards Applicationsmentioning
confidence: 99%
“…Similar tuning of the effective magnetic flux in ring-shaped lattices enables the observation of the Hofstadter butterfly via the lattice's scattering resonances [78,79]. There are recent proposals to implement phase shifters throughout the entire lattice in order to tune its topological properties, thereby enabling one to switch the topological edge states on or off or reroute them between different output ports [71,80,81]. Zhao et al [82] demonstrated controllable rerouting of topological states in the quantum Hall resonator lattice using structured bulk gain.…”
Section: Topological Coupled Resonator Latticesmentioning
confidence: 99%
“…Similar tuning of the effective magnetic flux in ring-shaped lattices enables the observation of the Hofstadter butterfly via the lattice's scattering resonances 69,70 . There are recent proposals to implement phase shifters throughout the entire lattice in order to tune its topological properties, thereby enabling one to switch the topological edge states on or off or reroute them between different output ports 60,71,72 . Zhao et al demonstrated controllable re-routing of topological states in the quantum Hall resonator lattice using structured bulk gain 73 .…”
Section: Topological Coupled Resonator Latticesmentioning
confidence: 99%